The activity demands and physiological responses observed in professional ballet: A systematic review - Shaw, J. W.; Mattiussi, A. M.; Brown, D. D.; Springham, M.; Pedlar, C. R.; Tallent, J. (The Journal of Sport and Exercise Science, 2021)
The aim of this study was to systematically review research into the activity demands and physiological responses observed in professional ballet. PubMed, Web of Science, SPORTDiscus, and ProQuest were searched for original research relating to 1) the session-specific activity demands of professional ballet, 2) the general activity demands of professional ballet, 3) the immediate physiological responses to professional ballet, or 4) the delayed physiological responses to professional ballet. From an initial 7672 studies, 22 met the inclusion criteria. Methodological quality was assessed using the Mixed Methods Appraisal Tool and a modified Downs and Black Index. Professional ballet is intermittent; however, activity characteristics and intensity vary by session type and company rank. Performances involve high volumes of jumps (5.0 } 4.9 jumpsEmin-1), plies (11.7 } 8.4 pliesEmin-1), and lifts (men - 1.9 } 3.3 liftsEmin-1), which may result in near-maximal metabolic responses. Ballet classes are less metabolically intense than performance during both barre and centre (< 50% V.O2max). Neither the activity demands nor the physiological responses encountered during rehearsals have been investigated. Day-to-day activity demands are characterized by high volumes of rehearsal and performance (> 5 hEday-1), but half is spent at intensities below 3 METs. Evidence is mixed regarding the delayed physiological responses to professional ballet; however, metabolic and musculoskeletal adaptations are unlikely to occur from ballet alone. The mean Downs and Black score was 62%. Appraisal tools revealed that a lack of clarity regarding sampling procedures, no power calculation, and a poor quality of statistical analysis were common limitations of the included studies. Given the large working durations and high rates of jumps, plies, and lifts, managing training loads and recovery may be a focus for strategies seeking to optimize dancer health and wellbeing. Ballet companies should provide dancers with opportunities and resources to engage in supplementary physical training. Further research is required into the physical demands of rehearsals and the longitudinal training loads undertaken by professional ballet dancers.